The Kinetics of Circulating Monocyte Subsets and Monocyte-Platelet Aggregates in the Acute Phase of ST-Elevation Myocardial Infarction: Associations with 2-Year Cardiovascular Events. Issue 18 (May 2016) - Zhou, Xin; Liu, Xin-Lin; Ji, Wen-Jie; Liu, Jun-Xiang; Guo, Zhao-Zeng; Ren, Dong; Ma, Yong-Qiang; Zeng, Shan; Xu, Zhong-Wei; Li, Hong-Xia; Wang, Peizhong Peter; Zhang, Zhuoli; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: In experimental myocardial infarction (MI), a rise in cell counts of circulating monocyte subsets contributes to impaired myocardial healing and to atherosclerotic plaque destabilization. In humans, the prognostic role of monocyte subsets in patients suffering ST-elevation MI (STEMI) is still unclear. In the present study, we aimed to determine the kinetics of the 3 monocyte subsets (classical CD14++CD16–, intermediate CD14++CD16+, and nonclassical CD14+CD16++ monocytes), as well as the subset-specific monocyte–platelet aggregates (MPA), in acute STEMI followed by primary percutaneous coronary intervention (PCI), and their relationships with cardiovascular outcomes during a 2-year follow-up. Monocyte subsets and MPA were measured in 100 STEMI patients receiving primary PCI on days 1, 2, 3, 5, and 7 of symptom onset, which were compared with 60 stable coronary heart disease patients and 35 healthy volunteers. From day 1 to day 7, significant increases in the counts of CD14++CD16+ monocytes and CD14++CD16+ MPA were observed, with peak levels on day 2. During a median follow-up of 2.0 years, 28 first cardiovascular events (defined as cardiovascular death, nonfatal ischemic stroke, recurrent MI, need for emergency or repeat revascularization, and rehospitalization for heart failure) were recorded. After adjustment for confounders, CD14++CD16+ monocytosis (day 1 [HR: 3.428; 95% CI: 1.597–7.358; P  = 0.002], day 2 [HR: 4.835; 95% CI: 1.106–21.13; P  = 0.04], day 3 [HR: 2.734; 95% CI: 1.138–6.564; P  = 0.02], and day 7 [HR: 2.647; 95% CI: 1.196–5.861; P  = 0.02]), as well as increased levels of CD14++CD16+ MPA measured on all time points (days 1, 2, 3, 5, and 7), had predictive values for adverse cardiovascular events. In conclusion, our data show the expansion of the CD14++CD16+ monocyte subset during acute phase of STEMI has predictive values for 2-year adverse cardiovascular outcomes in patients treated with primary PCI. Future studies will be warranted to elucidate whether CD14++CD16+ monocytes may become a target cell population for new therapeutic strategies after STEMI.